Front Cover Image, Volume 78, Issue 8. Issue 8 (14th July 2022) - Zhou, Qian; Li, Linwei; Liu, Fei; Hu, Jun; Cao, Yan; Qiao, Siwei; Zhou, Yuxin; Wang, Bi; Jia, Yihe; Chen, Yu; Xu, Shu; Feng, Xu
Abstract : The front cover image is based on the Research Article Mining and characterization of oxidative stress‐related binding proteins of parthenolide in Xanthomonas oryzae pv. oryzae by Qian Zhou et al., https://doi.org/10.1002/ps.6961 . Abstract : The front cover image is based on the Research Article Mining and characterization of oxidative stress‐related binding proteins of parthenolide in Xanthomonas oryzae pv. oryzae by Qian Zhou et al., https://doi.org/10.1002/ps.6961 .